The dynamic of policymaking process in Malaysia - Fazni Mat Arifin; Nooraini Othman (Penerbit Universiti Kebangsaan Malaysia, 2018)
The rapid progression in the new globalized world has caused significant transformation in policymaking process. Policymaking in developed countries have long moved towards new governance by becoming a more engaging in policy decision. While some views that Malaysia’s policy system is impeded by executive dominance, the country to some extent has opened the process to public opinion and participation. The paper thus intends to describe the development of policymaking process in Malaysia by examining three major factors that shape the policy process, namely the governmental structure which represents the system, the processes which are undertaken by the civil service in making policy and the governance which is closely connected with the wider public The research is qualitative in nature and shall use secondary data only. The investigation eventually informs the dynamic of policymaking process in the country. Malaysia superficially is not far behind the other developed countries, the country already has its own engagement system to produce an inclusive policy. The only limitation underneath is to have an appropriate methodological approach to complement the system, in which this would invite future research in the field.